CONTROL OF TWO SPECIES OF Colletotrichum CAUSING ANTHRACNOSE IN MARADOL PAPAYA FRUITS - Santamaría Basulto Felipe; Díaz Plaza Raúl; Gutiérrez Alonso Omar; Santamaría Fernández Jorge; Larqué Saavedra Alfonso (Revista Mexicana de Ciencias Agrícolas, 2018)
Anthracnose is a limitation of papaya fruits’ life, mainly caused by Colletotrichum gloeosporioides, although it is possible to find other Colletotrichum species causing diseases in the same crop. In order to control anthracnose in Yucatán, several fungicides are recommended, but not all of them are allowed by the Environmental Protection Agency (EPA) of the United States, the main country to which Yucatan’s papaya is exported. This study aimed to identify the causal agent of anthracnose of papaya in Yucatan, to evaluate the effect of fungicides that have EPA registration on species that cause anthracnose and to explore the effect of resistance inducers in controlling this disease. During March and May 2006, nine isolates of Colletotrichum were obtained from fruits of three producing regions of Yucatán, which were identified using taxonomic keys. The product evaluation was done by sensitivity in vitro bioassays and the effectiveness in inoculated fruits, ensuing in August 2007, November 2007 and February 2008, the effect of postharvest application of fungicides and resistance inducers on anthracnose on naturally infected fruits from the field were evaluated. In the three sites, two species that cause anthracnose were found and identified as C. gloeosporioides and C. dematium. Under in vitro conditions, C. gloeosporioides development was inhibited by prochloraz, ferbam, azoxystrobin, tryf loxystrobin and chlorothalonil; C. dematium development was inhibited only by prochloraz, ferbam and chlorothalonil. In inoculated fruits, prochloraz was 100% effective for both species, while azoxystrobin was 87.5% effective in C. gloeosporioides and 3.3% in C. dematium.